Scientific output after the 2017, 2019 and 2021 meetings of the Sociedad Española de Neonatología - Luis Bachiller Carnicero (Elsevier, 2024)
Introduction: The sharing of research findings through communications at congresses and publications is essential for the dissemination of scientific knowledge. The aim was to determine the percentage of communications presented the biennial meetings of the Sociedad Española de Neonatología (SENeo, Spanish Society of Neonatology) eventually published as full-text articles in indexed peer-reviewed journals and their bibliometric characteristics. Material and methods: We conducted a cross-sectional study by reviewing the abstracts from the oral communications (OCs) in the 2017, 2019 and 2021 SENeo congresses. Then we searched for the authors in the MEDLINE and Scopus databases. We collected data on the authors, type of OC and bibliometric characteristics. Results: The sample included 525 OCs, and we found a publication rate of 40.38% corresponding to 212 publications, 78.8% of them in international journals. The most frequent journal of publication was Anales de Pediatría. The median and interquartile range values for the impact factor, quartile and number of citations were 2.86 (1.96-3.98), 2 (1−3) and 3 (0−7), respectively, with a remarkable increase in the impact factor for the most recent congresses. The median time elapsed to publication was 10 months (IQR, 1-23). The proportion published was higher for multicentre studies and those with a respiratory topic. Conclusions: The frequency of publication for OCs submitted to SENeo congresses was similar to the frequency of publication for other paediatric congresses, with an impact factor that was above the mean of the congresses under study. The proportion of publication was higher for studies with a multicentre design or a respiratory topic. Resumen: Introducción: La divulgación de una investigación, mediante comunicaciones en congresos y publicaciones en revistas científicas resulta fundamental para la transmisión del conocimiento adquirido. El objetivo del estudio fue determinar el porcentaje de comunicaciones de los congresos de la Sociedad Española de Neonatología (SENeo) que son publicados en revistas indexadas y sus características bibliométricas. Material y métodos: Se diseñó un estudio transversal, obteniendo datos de las comunicaciones orales (CO) presentadas en los congresos de la SENeo de 2017, 2019 y 2021. Se realizó búsqueda por autor en Medline y Scopus. Se recogieron datos sobre los autores, tipo de CO y características bibliométricas. Resultados: Fueron recopiladas 525 CO con una tasa de publicación de 40,38% (212 publicaciones), correspondiendo un 78,8% a una revista internacional. Anales de Pediatría fue la revista más utilizada. Las medianas y rangos intercuartílicos del factor de impacto, cuartil y número de citaciones fueron de de 2,86 (1,96−3,98); 2 (1−3) y 3 (0−7), respectivamente, con un progresivo aumento del factor de impacto en los últimos congresos. El lapso hasta la publicación tuvo una mediana de 10 meses (RI: 1-23). La tasa de publicación fue mayor en caso de temática respiratoria y estudios multicéntricos. Conclusiones: Las CO enviadas a los congresos de la SENeo tuvieron una tasa de publicación similar a otros congresos pediátricos, obteniendo un impacto en la literatura superior a la media de los congresos estudiados. Los estudios multicéntricos y aquellos sobre temática respiratoria obtuvieron mayor tasa de publicación.